Silicon-based electrode active material, electrode composite active material, preparation method and application
By introducing high-conductivity conductive substances into the silicon-based electrode active material and adhering to the silicon-based particles through an adhesive layer, the problem of unstable conductive connections of the silicon-based electrode active material during charging and discharging is solved, and the dynamic performance and capacity retention rate of the battery are improved.
Patent Information
- Application Number
- CN202412000104.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
AI Technical Summary
The expansion and contraction of silicon-based electrode active materials during charging and discharging leads to unstable conductive connections, affecting the dynamic performance and capacity retention of the battery.
A stable conductive connection is established by introducing conductive substances with higher conductivity than silicon-based particles into the silicon-based electrode active material and adhering them to the silicon-based particles through an adhesive layer, ensuring that adhesion is maintained during expansion and contraction.
The lithium storage activity and kinetic performance of silicon-based electrode active materials are improved, and the capacity retention rate of charge and discharge cycles is enhanced.
Smart Images

Figure CN119695132A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a silicon-based electrode active material, an electrode composite active material, a preparation method and an application. Background Art
[0002] As electronic devices pursue longer battery life and thinner size, higher demands are placed on the energy density of batteries. Traditional graphite materials have a theoretical specific capacity of 372mAh / g, which is relatively low and has been developed to a value close to the theoretical value. Therefore, the continued use of traditional graphite negative electrode systems limits the further improvement of battery energy density, and the development of the next generation of negative electrode materials is urgently needed.
[0003] Silicon material has a theoretical specific capacity of 4200mAh / g and is the most promising negative electrode material for the next generation of high energy density batteries. However, the cycle performance of silicon material is poor and cannot meet market demand. Summary of the invention
[0004] Based on this, the present application provides a silicon-based electrode active material, an electrode composite active material, a preparation method and an application.
[0005] The first aspect of the present application provides a silicon-based electrode active material, and its technical solution is as follows:
[0006] A silicon-based electrode active material comprises silicon-based particles, an adhesive layer and a conductive substance, wherein the conductivity of the conductive substance is greater than that of the silicon-based particles, the conductive substance is attached to the silicon-based particles through the adhesive layer, and can remain attached to the silicon-based particles during the expansion and contraction of the silicon-based particles.
[0007] The second aspect of the present application provides an electrode composite active material, and its technical solution is as follows:
[0008] An electrode composite active material comprises the silicon-based electrode active material and active particles as described above, wherein the active particles are independently and freely dispersed in the gaps of the silicon-based electrode active material, or are coated by the bonding layer, or are connected to the silicon-based particles through the bonding layer.
[0009] The third aspect of the present application provides a method for preparing a silicon-based electrode active material, and the technical solution thereof is as follows:
[0010] A method for preparing a silicon-based electrode material comprises the following steps:
[0011] mixing silicon-based particles and a conductive substance to obtain a dry powder mixture, wherein the conductive substance has a greater conductivity than the silicon-based particles;
[0012] Mixing the dry powder mixture, the binding material and the solvent to obtain a slurry having a solid content of 50 wt % to 90 wt %;
[0013] After diluting the slurry, the solvent is removed, so that the bonding material forms a bonding layer, and the bonding layer attaches the conductive substance to the silicon-based particles and enables the conductive substance to remain attached to the silicon-based particles during the expansion and contraction of the silicon-based particles.
[0014] The fourth aspect of the present application provides a method for preparing an electrode composite active material, and its technical solution is as follows:
[0015] A method for preparing an electrode composite active material comprises the following steps: mixing a silicon-based electrode active material and active particles, wherein the silicon-based electrode active material is as described above, or is prepared by the preparation method as described above.
[0016] The fifth aspect of the present application provides a method for preparing an electrode composite active material, and the technical solution thereof is as follows:
[0017] A method for preparing an electrode composite active material comprises the following steps:
[0018] mixing silicon-based particles, a portion of active particles and a conductive substance to obtain a dry powder mixture, wherein the conductive substance has a greater conductivity than the silicon-based particles;
[0019] Mixing the dry powder mixture, the binding material and the solvent to obtain a slurry having a solid content of 50 wt % to 90 wt %;
[0020] After diluting the slurry, the solvent is removed, so that the bonding material forms a bonding layer, the bonding layer attaches the conductive substance to the silicon-based particles, and enables the conductive substance to remain attached to the silicon-based particles during the expansion and contraction of the silicon-based particles, and the active particles are coated by the bonding layer, or connected to the silicon-based particles through the bonding layer, or connected to the conductive substance through the bonding layer, to obtain a premixed powder;
[0021] Mix the premixed powder with the remaining portion of the active particles.
[0022] The sixth aspect of the present application provides a method for preparing an electrode composite active material, and its technical solution is as follows:
[0023] A method for preparing an electrode composite active material comprises the following steps:
[0024] mixing silicon-based particles, active particles and a conductive substance to obtain a dry powder mixture, wherein the conductive substance has a greater conductivity than the silicon-based particles;
[0025] Mixing the dry powder mixture, the binding material and the solvent to obtain a slurry having a solid content of 50 wt % to 90 wt %;
[0026] After diluting the slurry, the solvent is removed, so that the bonding material forms a bonding layer, and the bonding layer attaches the conductive substance to the silicon-based particles, and enables the conductive substance to remain attached to the silicon-based particles during the expansion and contraction of the silicon-based particles, and the active particles are coated by the bonding layer, or connected to the silicon-based particles through the bonding layer, or connected to the conductive substance through the bonding layer.
[0027] The seventh aspect of the present application provides an electrode plate, and its technical solution is as follows:
[0028] An electrode plate comprises a current collector and an electrode active layer located on the current collector, wherein the electrode active layer comprises the silicon-based electrode active material as described above, or comprises the electrode composite active material as described above, or comprises the silicon-based electrode active material prepared by the preparation method as described above, or comprises the electrode composite active material prepared by the preparation method as described above.
[0029] In an eighth aspect, the present application provides a battery, and its technical solution is as follows:
[0030] A battery comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and the negative electrode sheet is as described above, or comprises the silicon-based electrode active material as described above, or comprises the electrode composite active material as described above, or comprises the silicon-based electrode active material prepared by the preparation method as described above, or comprises the electrode composite active material prepared by the preparation method as described above.
[0031] This application has the following beneficial effects:
[0032] After research, the present application found that the cycle performance of silicon-based pole pieces is related to the unstable conductive connection between silicon-based electrode active materials. Specifically: silicon-based electrode active materials and active particles are usually blended, and the active particles are filled in the gaps between silicon-based electrode active materials. During the charge and discharge process, the silicon-based electrode active materials will have a large expansion and contraction, and a large gap will be generated between the surrounding active particles. This gap will lead to increased polarization, and even some silicon-based electrode active materials will completely lose the conductive connection, lose lithium storage activity, and cause the kinetic performance to decrease, the capacity to decrease, and even lithium precipitation reaction to occur. Based on the above findings, the present application introduces a conductive substance with a conductivity greater than that of silicon-based particles into the silicon-based electrode active material through an adhesive layer. The conductive substance not only adheres to the silicon-based particles, but also maintains its attachment to the silicon-based particles during the expansion and contraction of the silicon-based particles during charge and discharge. In this way, the conductive substance can play the role of a bridge, and during the charge and discharge process, a stable conductive connection is generated between the silicon-based electrode active materials. At the same time, the conductive substance can also span the gap between the silicon-based particles and the active particles to enhance the conductive connection between the two. The silicon-based electrode active material of the present application has good lithium storage activity and kinetic performance, and a high capacity retention rate during charge and discharge cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.
[0034] Figure 1 is a schematic structural diagram of a silicon-based electrode active material according to one embodiment;
[0035] Figure 2 A schematic diagram of the structure of an electrode composite active material according to one embodiment;
[0036] Figure 3 is a SEM image of the silicon-based electrode active material of Example 1;
[0037] Figure 4 This is the SEM image of the premixed powder of Example 4;
[0038] Figure 5 This is a SEM image of the electrode of Example 1 before buckling power cycle;
[0039] Figure 6 This is the SEM image of the electrode of Example 1 after the buckling cycle. DETAILED DESCRIPTION
[0040] The present application will be further described in detail below in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present application more thoroughly understood.
[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0042] the term
[0043] Unless otherwise specified or there is a contradiction, the terms and phrases used in this application have the following meanings:
[0044] In this application, "optionally", "optional" and "optional" refer to optional, that is, to any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.
[0045] In this application, in the "first aspect", "second aspect", "third aspect", "fourth aspect", etc., the terms "first", "second", "third", "fourth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0046] In the present application, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or that the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being “above”, “above”, and “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, and “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0047] In the present application, when an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or there may also be an intermediate element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be an intermediate element at the same time. It should also be understood that when explaining the connection relationship or positional relationship of elements, although not explicitly described, the connection relationship and positional relationship are interpreted as including an error range, which should be within the acceptable deviation range of a specific value determined by a person skilled in the art.
[0048] In a first aspect, the present application provides a silicon-based electrode active material. In one embodiment, the silicon-based electrode active material includes silicon-based particles, a bonding layer and a conductive substance. The conductivity of the conductive substance is greater than that of the silicon-based particles. The conductive substance is attached to the silicon-based particles through the bonding layer and can remain attached to the silicon-based particles during the expansion and contraction of the silicon-based particles.
[0049] The inventors have found that the cycle performance of silicon-based pole pieces is related to the unstable conductive connection between silicon-based electrode active materials. Specifically: silicon-based electrode active materials and active particles are usually blended, and the active particles are filled in the gaps between silicon-based electrode active materials. During the charge and discharge process, the silicon-based electrode active materials will have a large expansion and contraction, and a large gap will be generated between the surrounding active particles. This gap will lead to increased polarization, and even some silicon-based electrode active materials will completely lose the conductive connection, lose the lithium storage activity, and cause the kinetic performance to decrease, the capacity to decrease, and even lithium precipitation reaction to occur. Based on the above findings, the above embodiment introduces a conductive substance with a conductivity greater than that of the silicon-based particles into the silicon-based electrode active material through the bonding layer. The conductive substance not only adheres to the silicon-based particles, but also maintains its attachment to the silicon-based particles during the expansion and contraction of the silicon-based particles during charge and discharge. In this way, the conductive substance can play the role of a bridge, and during the charge and discharge process, a stable conductive connection is generated between the silicon-based electrode active materials. At the same time, the conductive substance can also span the gap between the silicon-based particles and the active particles to enhance the conductive connection between the two. The silicon-based electrode active material of the above embodiment has good lithium storage activity and kinetic performance, and a high capacity retention rate during charge and discharge cycles.
[0050] In the above embodiment, the adhesive layer can prevent the conductive material from falling off the silicon-based particles, and the conductive material can be attached to the silicon-based particles in various ways. Optionally, the adhesive layer covers the silicon-based particles. Optionally, the conductive material is independently dispersed in the adhesive layer, or is located on the surface of the adhesive layer, or is covered by the adhesive layer.
[0051] See also Figure 1, is a schematic structural diagram of a silicon-based electrode active material according to an embodiment. The silicon-based electrode active material 100 includes silicon-based particles 11, a bonding layer 12 and a conductive substance 13. The bonding layer 12 covers the silicon-based particles 11, and the conductive substance 13 is independently located on the outer surface of the bonding layer 12.
[0052] Optionally, the silicon-based particles include silicon and other elements, and the silicon content is 5wt% to 95wt%. For example, the silicon content is 5wt%, 10wt%, 25wt%, 50wt%, 65wt%, 80wt%, and 95wt%. Optionally, the other elements include one or more of carbon, nitrogen, oxygen, fluorine, chlorine, phosphorus, sulfur, boron, copper, silver, titanium, zirconium, vanadium, molybdenum, tungsten, aluminum, and iron. The sum of the content of silicon and the content of other elements is 100%.
[0053] Optionally, the particle size D50 of the silicon-based particles satisfies: 0.1 μm ≤ D50 ≤ 30 μm. For example, the particle size D50 is 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, or 30 μm. The silicon-based particles may be spherical.
[0054] Optionally, the mass of the conductive substance accounts for 0.04% to 50% of the mass of the silicon-based electrode active material, for example, 0.04%, 0.5%, 1%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 40%, 50%.
[0055] Optionally, the conductive material includes one or more of conductive carbon black, carbon nanotubes, graphene, carbon fibers, copper nanoparticles and silver nanoparticles.
[0056] The size of the conductive material can be adjusted and selected according to the shape of the conductive material. Optionally, the conductive material is irregular in shape, and the particle size D50 satisfies: 0.01μm≤D50≤10μm. For example, the particle size D50 is 0.5μm, 1μm, 5μm, 10μm. Optionally, the conductive material is spherical, and the particle size D50 satisfies: 0.01μm≤D50≤10μm. For example, the particle size D50 is 0.5μm, 1μm, 5μm, 10μm. Optionally, the conductive material is fibrous or tubular, and the average length L satisfies: 0.5μm≤D50≤100μm, and the aspect ratio L / D satisfies: 1≤D50≤200000. For example, the length L is 0.5μm, 1μm, 5μm, 10μm, 50μm, 100μm. The aspect ratio L / D is 1, 10, 100, 1000, 10000, 100000, 200000. Optionally, the conductive material is in sheet form, and the thickness h satisfies: 0.1nm≤h≤10μm. For example, the thickness h is 0.1nm, 1nm, 10nm, 100nm, 1μm, 10μm. The maximum distance L1 between two points on the front side satisfies: 0.05μm≤L1≤100μm. For example, L1 is 0.05μm, 0.5μm, 5μm, 50μm, 100μm. The maximum distance L2 between two points on the back side satisfies: 0.05μm≤L2≤100μm. For example, L2 is 0.05μm, 0.5μm, 5μm, 50μm, 100μm. Optionally, the conductive material is in a strip shape, with a thickness h satisfying: 0.1nm≤h≤10μm, and an average length L satisfying: 0.05μm≤L≤100μm. For example, L is 0.05μm, 0.5μm, 5μm, 50μm, 100μm. The average width W satisfies: 1nm≤W≤50μm. For example, the average width W is 1nm, 10nm, 100nm, 1μm, 10μm, 50μm.
[0057] Optionally, the mass of the bonding layer accounts for 0.04% to 50% of the mass of the silicon-based electrode active material, for example, 0.04%, 0.5%, 1%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 40%, 50%.
[0058] Optionally, the material of the bonding layer includes one or more of a polymer bonding material, a partial carbide of the polymer bonding material, and a complete carbide of the polymer bonding material, wherein the partial carbide and the complete carbide of the polymer bonding material are formed by heating and carbonizing part or all of the polymer bonding material.
[0059] Optionally, the structure of the polymer adhesive material includes one or more of an acrylate group, a carboxylic acid group, a cyano group, an amide group, a hydroxyl group, a benzene ring, a carbon-carbon double bond, a carbon-carbon triple bond, a pyrrole, an amine group, and an imine group. For example, the polymer adhesive material includes one or more of PAA (polyacrylic acid), CMC (carboxymethyl cellulose), SBR (styrene-butadiene rubber), PAN (polyacrylonitrile), PAM (polyacrylamide), PVA (polyvinyl alcohol), PPy (polypyrrole), and PANI (polyaniline). The above polymer adhesive material can be a conductive polymer adhesive material, a semi-conductive polymer adhesive material, or an insulating polymer adhesive material.
[0060] Optionally, the specific surface area of the silicon-based electrode active material is ≤30m 2 / g. For example, the specific surface area is 5m 2 / g, 10m 2 / g, 15m 2 / g, 20m 2 / g, 25m 2 / g, 30m 2 / g.
[0061] Optionally, the particle size D10 of the primary particles of the silicon-based electrode active material satisfies: 0.01 μm ≤ D10 ≤ 50 μm. The particle size D50 satisfies: 0.01 μm ≤ D50 ≤ 50 μm. The particle size D90 satisfies: 0.01 μm ≤ D90 ≤ 50 μm. For example, D10 is 0.01 μm, 1 μm, 10 μm, 50 μm. D50 is 0.01 μm, 1 μm, 10 μm, 50 μm. D90 is 0.01 μm, 1 μm, 10 μm, 50 μm.
[0062] Optionally, the particle size D50 of the secondary particles of the silicon-based electrode active material satisfies: 0.15 μm ≤ D50 ≤ 100 μm. For example, D50 is 0.15 μm, 0.2 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 50 μm, 80 μm, or 100 μm.
[0063] Optionally, the resistivity of the silicon-based electrode active material is 0.5 Ω·mm to 1500 Ω·mm, for example, the resistivity is 0.5 Ω·mm, 1 Ω·mm, 10 Ω·mm, 100 Ω·mm, 1000 Ω·mm, 1500 Ω·mm.
[0064] Optionally, the silicon-based electrode active material is a silicon-based negative electrode active material.
[0065] The second aspect of the present application provides an electrode composite active material. In one embodiment, the electrode composite active material includes the silicon-based electrode active material and active particles as described above. It is beneficial to further improve the electrochemical performance of the silicon-based electrode active material. Optionally, the active particles are independently and freely dispersed in the gaps of the silicon-based electrode active material, or are coated by the bonding layer, or are connected to the silicon-based particles through the bonding layer, or are connected to the conductive material through the bonding layer.
[0066] The active particles have a certain theoretical specific capacity and a high electrical conductivity. The addition of active particles can further enhance the stability of the conductive connection. The active particles can exist in a variety of ways. It can be understood that the active particles are freely dispersed in the gaps between the silicon-based electrode active materials, which means that the active particles can be spaced or in direct contact with the silicon-based particles, and there is no restriction on the position of the active particles. This state can be achieved by blending the silicon-based electrode active materials and the active particles. In addition, the active particles can also be coated with the bonding layer, or connected to the silicon-based particles through the bonding layer, or connected to the conductive material through the bonding layer. In this case, it can be achieved by preparing a premixed powder.
[0067] The active particles are coated with a bonding layer. At this time, the bonding layer can coat the active particles alone or coat the silicon-based particles and the active particles at the same time. When the silicon-based particles and the active particles are coated at the same time, it is equivalent to "bundling" the silicon-based particles and the active particles. After the silicon-based particles and the active particles are "bundled", a direct conductive connection is formed between the two, and during the charge and discharge process, the expanded silicon-based material can also maintain a conductive connection with the active particles. And because the active particles have a small expansion rate in a certain direction when fully embedded with lithium, it is more conducive to maintaining electrical connection with the surrounding system in this direction, thereby providing a more stable conductive structure to maintain the capacity retention rate and kinetic performance during the cycle. In addition, when the active particles are connected to the silicon-based particles through the bonding layer, it is also conducive to the above-mentioned role. When the active particles are connected to the conductive material through the bonding layer, and the conductive material is connected to the silicon-based particles through the bonding layer, it is also conducive to the above-mentioned role.
[0068] Optionally, the bonding layer covers the silicon-based particles and the active particles. When the bonding layer covers the silicon-based particles and the active particles, the conductive connection between the two is more stable, and the conductive substance can still be attached to the silicon-based particles in a variety of ways. Optionally, the conductive substance is independently dispersed in the bonding layer, or is located on the surface of the bonding layer, or is coated by the bonding layer.
[0069] See also Figure 2, is a schematic structural diagram of an electrode composite active material according to an embodiment. The electrode composite active material 200 includes silicon-based particles 21, a bonding layer 22, a conductive substance 23 and active particles 24. The bonding layer 22 covers the silicon-based particles 21 and the active particles 24, and the conductive substance 23 is independently located on the outer surface of the bonding layer 22.
[0070] Optionally, each of the active particles meets the following conditions:
[0071] 1) The theoretical specific capacity of the active particles is ≥ 100 mAh / g;
[0072] 2) The electrical conductivity of the active particles is greater than that of the silicon-based particles;
[0073] 3) The expansion rate of the active particles in a certain direction when fully intercalated with lithium is smaller than the expansion rate of the silicon-based particles in the same direction when fully intercalated with lithium.
[0074] Optionally, the active particles account for 1% to 95% of the mass of the silicon-based electrode material, for example, 1%, 25%, 50%, 75%, 95%.
[0075] Optionally, the active particles include one or more of artificial graphite, natural graphite, hard carbon, soft carbon, carbon microspheres, lithium metal, lithium titanate, silicon-based materials and tin-based materials. It is understood that when the active particles are silicon-based materials, the elements or contents of the silicon-based materials are different from those of the silicon-based particles.
[0076] Optionally, the particle size D50 of the active particles satisfies: 0.1 μm ≤ D50 ≤ 50 μm. For example, D50 is 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 50 μm. The active particles may be spherical.
[0077] It can be understood that the electrode composite active material is a negative electrode composite active material.
[0078] A third aspect of the present application provides a method for preparing a silicon-based electrode active material. In one embodiment, the method for preparing a silicon-based electrode material comprises the following steps:
[0079] mixing silicon-based particles and a conductive substance to obtain a dry powder mixture;
[0080] Mixing the dry powder mixture, the binding material and the solvent to obtain a slurry having a solid content of 50 wt % to 90 wt %;
[0081] After diluting the slurry, the solvent is removed, so that the bonding material forms a bonding layer, and the bonding layer attaches the conductive substance to the silicon-based particles, and enables the conductive substance to remain attached to the silicon-based particles during the expansion and contraction of the silicon-based particles, wherein the conductivity of the conductive substance is greater than that of the silicon-based particles.
[0082] In the process of mixing raw materials, the dry powder is mixed first and then the solid content of the slurry is controlled, which is beneficial to the preparation of silicon-based electrode active materials with better adhesion of conductive substances and is beneficial to the adhesion of conductive substances during the expansion and contraction of silicon-based particles.
[0083] The solid content of the slurry can be 50wt%, 60wt%, 70wt%, 80wt%, or 90wt%. This solid content range is conducive to sufficient mixing of the raw materials to form a structure coated with a bonding layer.
[0084] The silicon-based particles and the conductive material are as described above and will not be described in detail here.
[0085] Optionally, the structure of the bonding material includes one or more of an acrylate group, a carboxylic acid group, a cyano group, an amide group, a hydroxyl group, a benzene ring, a carbon-carbon double bond, a carbon-carbon triple bond, a pyrrole, an amine group, and an imine group. For example, the polymer bonding material includes one or more of PAA (polyacrylic acid), CMC (carboxymethyl cellulose), SBR (styrene-butadiene rubber), PAN (polyacrylonitrile), PAM (polyacrylamide), PVA (polyvinyl alcohol), PPy (polypyrrole), and PANI (polyaniline). The above polymer bonding material can be a conductive polymer bonding material, a semi-conductive polymer bonding material, or an insulating polymer bonding material.
[0086] Optionally, the mass of the bonding material accounts for 0.04% to 50% of the mass of the silicon-based electrode active material, for example, 0.04%, 0.5%, 1%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 40%, 50%.
[0087] Optionally, the solvent includes water. Optionally, the method for removing the solvent includes spray drying. Optionally, before spray drying, the following steps are also included: diluting the slurry to a solid content of 1wt% to 50wt%. For example, diluting to a solid content of 1wt%, 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%. The above solid content range is conducive to spray drying. It is understandable that the diluent solvent can be removed by spray drying. Optionally, the diluent includes water.
[0088] After removing the solvent, the bonding material can form a bonding layer, and at this time, the bonding layer does not contain carbides. Optionally, after removing the solvent, the following steps are also included, heating to partially or completely carbonize the bonding material to form the bonding layer. By heating, a part or all of the bonding material is carbonized to form carbides, and at this time the bonding layer includes partial carbides or complete carbides. The bonding layer includes partial carbides or complete carbides, which is more conducive to improving the electrical conductivity of the electrode active material.
[0089] The carbonization degree of the bonding layer is related to the heating temperature. Optionally, the heating temperature is 60°C to 700°C. For example, the heating temperature is 60°C, 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C.
[0090] The fourth aspect of the present application provides a method for preparing an electrode composite active material. In one embodiment, the method for preparing an electrode composite active material comprises the following steps: mixing a silicon-based electrode active material and active particles, wherein the silicon-based electrode active material is as described above, or is prepared by the preparation method as described above.
[0091] The active particles have a certain theoretical specific capacity and high electrical conductivity. The addition of active particles can further enhance the stability of the conductive connection.
[0092] Optionally, the active particles account for 1% to 95% of the mass of the silicon-based electrode material, for example, 1%, 25%, 50%, 75%, 95%.
[0093] A fifth aspect of the present application provides a method for preparing an electrode active composite material. In one embodiment, the method for preparing an electrode composite active material comprises the following steps:
[0094] A method for preparing an electrode composite active material comprises the following steps:
[0095] mixing silicon-based particles, a portion of active particles and a conductive substance to obtain a dry powder mixture, wherein the conductive substance has a greater conductivity than the silicon-based particles;
[0096] Mixing the dry powder mixture, the binding material and the solvent to obtain a slurry having a solid content of 50 wt % to 90 wt %;
[0097] After diluting the slurry, the solvent is removed, so that the bonding material forms a bonding layer, the bonding layer attaches the conductive substance to the silicon-based particles, and enables the conductive substance to remain attached to the silicon-based particles during the expansion and contraction of the silicon-based particles, and the active particles are coated by the bonding layer, or connected to the silicon-based particles through the bonding layer, or connected to the conductive substance through the bonding layer, to obtain a premixed powder;
[0098] Mix the premixed powder with the remaining portion of the active particles.
[0099] Compared with blending silicon-based electrode active materials and active particles, the preparation of the above-mentioned premixed powder can more tightly bond a portion of the active particles, silicon-based particles and conductive substances, so that a portion of the active particles are coated by the bonding layer, or connected to the silicon-based particles through the bonding layer, or connected to the conductive substance through the bonding layer.
[0100] After removing the solvent, the bonding material can form a bonding layer, and at this time, the bonding layer does not contain carbides. Optionally, after removing the solvent, the following steps are also included, heating to partially or completely carbonize the bonding material to form the bonding layer. By heating, a part or all of the bonding material is carbonized to form carbides, and at this time the bonding layer includes partial carbides or complete carbides. The bonding layer includes partial carbides or complete carbides, which is more conducive to improving the conductive properties of the premixed powder.
[0101] Optionally, the active particles account for 1% to 95% of the total mass of the silicon-based particles, the bonding layer and the conductive material, for example, 1%, 25%, 50%, 75%, 95%.
[0102] Optionally, the particle size D10 of the primary particles of the premixed powder satisfies: 0.01 μm ≤ D10 ≤ 50 μm. The particle size D50 satisfies: 0.01 μm ≤ D50 ≤ 50 μm. The particle size D90 satisfies: 0.01 μm ≤ D90 ≤ 50 μm. For example, D10 is 0.01 μm, 1 μm, 10 μm, 50 μm. D50 is 0.01 μm, 1 μm, 10 μm, 50 μm. D90 is 0.01 μm, 1 μm, 10 μm, 50 μm.
[0103] Optionally, the resistivity of the premixed powder is 0.5 Ω·mm to 1500 Ω·mm. For example, the resistivity is 0.5 Ω·mm, 1 Ω·mm, 10 Ω·mm, 100 Ω·mm, 1000 Ω·mm, or 1500 Ω·mm.
[0104] It is understandable that other information of the active particles is as described above and will not be repeated here. The silicon-based particles, the conductive material, and the bonding material are as described above and will not be repeated here. Except for adding the active particles, the other steps refer to the preparation method of the silicon-based electrode active material described above and will not be repeated here.
[0105] A sixth aspect of the present application provides a method for preparing an electrode composite active material. In one embodiment, the method for preparing an electrode composite active material comprises the following steps:
[0106] mixing silicon-based particles, active particles and a conductive substance to obtain a dry powder mixture, wherein the conductive substance has a greater conductivity than the silicon-based particles;
[0107] Mixing the dry powder mixture, the binding material and the solvent to obtain a slurry having a solid content of 50 wt % to 90 wt %;
[0108] After diluting the slurry, the solvent is removed, so that the bonding material forms a bonding layer, and the bonding layer attaches the conductive substance to the silicon-based particles, and enables the conductive substance to remain attached to the silicon-based particles during the expansion and contraction of the silicon-based particles, and the active particles are coated by the bonding layer, or connected to the silicon-based particles through the bonding layer, or connected to the conductive substance through the bonding layer.
[0109] Compared with blending silicon-based electrode active materials and active particles, the preparation of the above-mentioned electrode composite active material can more closely bond the active particles, silicon-based particles and conductive substances, so that the active particles are coated by the bonding layer, or connected to the silicon-based particles through the bonding layer, or connected to the conductive substance through the bonding layer.
[0110] After removing the solvent, the bonding material can form a bonding layer, and at this time, the bonding layer does not contain carbides. Optionally, after removing the solvent, the following steps are also included, heating to partially or completely carbonize the bonding material to form the bonding layer. By heating, a part or all of the bonding material is carbonized to form carbides, and at this time the bonding layer includes partial carbides or complete carbides. The bonding layer includes partial carbides or complete carbides, which is more conducive to improving the conductive properties of the electrode composite active material.
[0111] Optionally, the active particles account for 1% to 95% of the total mass of the silicon-based particles, the bonding layer and the conductive material, for example, 1%, 25%, 50%, 75%, 95%.
[0112] Optionally, the particle size D10 of the primary particles of the electrode composite active material satisfies: 0.01 μm ≤ D10 ≤ 50 μm. The particle size D50 satisfies: 0.01 μm ≤ D50 ≤ 50 μm. The particle size D90 satisfies: 0.01 μm ≤ D90 ≤ 50 μm. For example, D10 is 0.01 μm, 1 μm, 10 μm, 50 μm. D50 is 0.01 μm, 1 μm, 10 μm, 50 μm. D90 is 0.01 μm, 1 μm, 10 μm, 50 μm.
[0113] Optionally, the resistivity of the electrode composite active material is 0.5 Ω·mm to 1500 Ω·mm. For example, the resistivity is 0.5 Ω·mm, 1 Ω·mm, 10 Ω·mm, 100 Ω·mm, 1000 Ω·mm, or 1500 Ω·mm.
[0114] It is understandable that other information of the active particles is as described above and will not be repeated here. The silicon-based particles, the conductive material, and the bonding material are as described above and will not be repeated here. Except for adding the active particles, the other steps refer to the preparation method of the silicon-based electrode active material described above and will not be repeated here.
[0115] The seventh aspect of the present application provides an electrode plate. In one embodiment, the electrode plate includes a current collector and an electrode active layer located on the current collector, and the electrode active layer includes the silicon-based electrode active material as described above, or includes the electrode composite active material as described above, or includes the silicon-based electrode active material prepared by the preparation method as described above, or includes the electrode composite active material prepared by the preparation method as described above.
[0116] Optionally, the electrode active layer further comprises a conductive agent and a binder. The conductive agent fills the gaps between the silicon-based electrode active materials to make the flow of current smoother. Optionally, the conductive agent comprises SP, CNT, graphene. Optionally, the binder comprises PAA.
[0117] It can be understood that the electrode plate is a negative electrode plate.
[0118] An eighth aspect of the present application provides a battery. In one embodiment, the battery includes a positive electrode plate, a negative electrode plate and a separator, wherein the separator is located between the positive electrode plate and the negative electrode plate, and the negative electrode plate is as described above, or includes the silicon-based electrode active material as described above, or includes the electrode composite active material as described above, or includes the silicon-based electrode active material prepared by the preparation method as described above, or includes the electrode composite active material prepared by the preparation method as described above.
[0119] It will be appreciated that the battery may be a lithium-ion battery.
[0120] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.
[0121] Among them, the silicon-based material is silicon-based particles, the silicon-based negative electrode material is silicon-based electrode material, and the negative electrode composite active material is electrode composite active material.
[0122] Example 1
[0123] This embodiment provides a silicon-based negative electrode material, a negative electrode composite active material and a preparation method thereof, the steps are as follows:
[0124] Step 1: Add 100 g of silicon-based material and 1 g of conductive carbon black into a mixing machine, and stir the dry powder for 30 minutes to obtain a dry powder mixture.
[0125] Step 2: Add 5 g of 10 wt % PAA aqueous solution, 25 g of 0.4 wt % CNT aqueous solution and 50 g of pure water to the dry powder mixture, knead and stir for 30 min to obtain a slurry with a solid content of 65 wt %.
[0126] Step 3: Add pure water to the slurry to dilute it to a solid content of 15 wt %, and spray dry it to obtain a solid powder.
[0127] Step 4: Heat the solid powder at 100° C. for 2 h, and obtain the silicon-based negative electrode active material 1 after cooling.
[0128] Step 5: Mix the silicon-based negative electrode active material 1 and graphite in a mass ratio of 10:90 to obtain a negative electrode composite active material 1.
[0129] Example 2
[0130] This embodiment provides a silicon-based negative electrode material, a negative electrode composite active material and a preparation method thereof, the steps are as follows:
[0131] Step 1: Add 100 g of silicon-based material and 1 g of conductive carbon black into a mixing machine, and stir the dry powder for 30 minutes to obtain a dry powder mixture.
[0132] Step 2: Add 5 g of 10 wt % PAA aqueous solution, 25 g of 0.4 wt % CNT aqueous solution and 50 g of pure water to the dry powder mixture, knead and stir for 30 min to obtain a slurry with a solid content of 65 wt %.
[0133] Step 3: Add 300 g of pure water to the slurry, dilute it to a solid content of 15 wt%, and spray dry it to obtain a solid powder.
[0134] Step 4: Heat the solid powder at 500° C. for 2 h, and obtain the silicon-based negative electrode active material 2 after cooling.
[0135] Step 5: Mix the silicon-based negative electrode active material 2 and graphite in a mass ratio of 10:90 to obtain a negative electrode composite active material 2.
[0136] Example 3
[0137] This embodiment provides a silicon-based negative electrode material, a negative electrode composite active material and a preparation method thereof, the steps are as follows:
[0138] Step 1: Add 100 g of silicon-based material and 1 g of carbon nanofiber into a mixer, and stir the dry powder for 30 minutes to obtain a dry powder mixture.
[0139] Step 2: Add 5 g of 10 wt % PAA aqueous solution, 5 g of 2 wt % graphene aqueous solution and 50 g of pure water to the dry powder mixture, knead and stir for 30 min to obtain a slurry with a solid content of 65 wt %.
[0140] Step 3: Add pure water to the slurry to dilute it to a solid content of 15 wt %, and spray dry it to obtain a solid powder.
[0141] Step 4: Heat the solid powder at 500° C. for 2 h, and obtain the silicon-based negative electrode active material 3 after cooling.
[0142] Step 5: Mix the silicon-based negative electrode active material 3 and graphite in a mass ratio of 10:90 to obtain a negative electrode composite active material 3.
[0143] Example 4
[0144] This embodiment provides a negative electrode composite active material and a preparation method thereof, the steps are as follows:
[0145] Step 1: Add 50 g of silicon-based material, 50 g of graphite and 1 g of conductive carbon black into a mixing mixer, and stir the dry powder for 30 minutes to obtain a dry powder mixture.
[0146] Step 2: Add 5 g of 10 wt % PAA aqueous solution, 25 g of 0.4 wt % CNT aqueous solution and 50 g of pure water to the dry powder mixture, knead and stir for 30 min to obtain a slurry with a solid content of 65 wt %.
[0147] Step 3: Add pure water to the slurry to dilute it to a solid content of 15 wt %, and spray dry it to obtain a solid powder.
[0148] Step 4: Heat the solid powder at 100° C. for 2 h, and obtain premixed powder 4 after cooling.
[0149] Step 5: Mix the premixed powder 4 with graphite in a mass ratio of 20:80 to obtain a negative electrode composite active material 4.
[0150] Example 5
[0151] This embodiment provides a negative electrode composite active material and a preparation method thereof, the steps are as follows:
[0152] Step 1: Add 30 g of silicon-based material, 70 g of hard carbon and 0.5 g of conductive carbon black into a mixing mixer, and stir the dry powder for 30 minutes to obtain a dry powder mixture.
[0153] Step 2: Add 5 g of 10 wt % PAA aqueous solution, 25 g of 0.4 wt % CNT aqueous solution, 5 g of 2 wt % graphene aqueous solution and 40 g of pure water to the dry powder mixture, knead and stir for 30 min to obtain a slurry with a solid content of 65 wt %.
[0154] Step 3: Add pure water to the slurry to dilute it to a solid content of 15 wt %, and spray dry it to obtain a solid powder.
[0155] Step 4: Heat the solid powder at 100° C. for 2 h, and obtain premixed powder 5 after cooling.
[0156] Step 5: Mix the premixed powder 5 with graphite in a mass ratio of 33.3:66.7 to obtain a negative electrode composite active material 5.
[0157] Example 6
[0158] This embodiment provides a negative electrode composite active material and a preparation method thereof, the steps are as follows:
[0159] Step 1: Add 30 g of silicon-based material, 70 g of graphite and 1 g of conductive carbon black into a mixing mixer, and stir the dry powder for 30 minutes to obtain a dry powder mixture.
[0160] Step 2: Add 10 g of 10 wt % PAA aqueous solution, 25 g of 0.4 wt % CNT aqueous solution and 50 g of pure water to the dry powder mixture, knead and stir for 30 min to obtain a slurry with a solid content of 65 wt %.
[0161] Step 3: Add pure water to the slurry to dilute it to a solid content of 15 wt %, and spray dry it to obtain a solid powder.
[0162] Step 4: Heat the solid powder at 500° C. for 2 h, and obtain premixed powder 6 after cooling.
[0163] Step 5: Mix the premixed powder 6 with graphite in a mass ratio of 33.3:66.7 to obtain a negative electrode composite active material 6.
[0164] Comparative Example 1
[0165] This comparative example provides a silicon-based negative electrode material, a negative electrode composite active material and a preparation method thereof, and the steps are as follows:
[0166] Step 1: Add 100 g of silicon-based material, 5 g of 10 wt% PAA aqueous solution and 50 g of pure water into a mixing machine, knead and stir for 30 minutes to obtain a slurry.
[0167] Step 2: Add pure water to the slurry to dilute it to a solid content of 15 wt %, and spray dry it to obtain a solid powder.
[0168] Step 3: Heat the solid powder at 100° C. for 2 h, and obtain the silicon-based negative electrode active material 7 after cooling.
[0169] Step 4: Mix the silicon-based negative electrode active material 7 and graphite in a mass ratio of 10:90 to obtain a negative electrode composite active material 7.
[0170] Comparative Example 2
[0171] This comparative example provides a silicon-based negative electrode material, a negative electrode composite active material and a preparation method thereof, and the steps are as follows:
[0172] Step 1: Add 100 g of silicon-based material, 1 g of conductive carbon black, 25 g of 0.4 wt% CNT aqueous solution and 50 g of pure water into a mixing machine, knead and stir for 30 minutes to obtain a slurry.
[0173] Step 2: Add pure water to the slurry to dilute it to a solid content of 15 wt %, and spray dry it to obtain a solid powder.
[0174] Step 3: Heat the solid powder at 100° C. for 2 h, and obtain the silicon-based negative electrode active material 8 after cooling.
[0175] Step 4: Mix the silicon-based negative electrode active material 8 and graphite in a mass ratio of 10:90 to obtain a negative electrode composite active material 8.
[0176] The silicon-based negative electrode materials or negative electrode composite active materials in the above embodiments and comparative examples were tested using the following method:
[0177] 1) The silicon-based negative electrode active materials in Examples 1, 2, 3 and Comparative Examples 1 and 2, and the premixed powders in Examples 4, 5 and 6 were tested for particle size distribution, and the D10, D50 and D90 of the measured primary particles are shown in Table 1. The silicon-based negative electrode active materials in Examples 1, 2, 3 and Comparative Examples 1 and 2, and the premixed powders in Examples 4, 5 and 6 were tested for resistivity using a four-probe method, and the measured powder resistivity is shown in Table 1.
[0178] 2) The negative electrode composite active materials of each embodiment and comparative example, SP, PAA and water were mixed to form a slurry, wherein SP accounted for 1% of the mass of the negative electrode composite active material and PAA accounted for 2% of the mass of the negative electrode composite active material. The slurry was coated on copper foil respectively, and the coated pole pieces were vacuum dried and rolled, and the rolled pole pieces were assembled into button-type half-cells, with the lithium sheet as the counter electrode. The button half-cell was subjected to rate and cycle tests: 0.1C discharge to 5mV, 0.02C discharge to 5mV, stand for 10min, 0.1C charge to 1.5V, stand for 10min; 1C discharge to 5mV, stand for 10min, 0.1C charge to 1.5V, stand for 10min; 2C discharge to 5mV, stand for 10min, 0.1C charge to 1.5V, stand for 10min; 0.5C discharge to 5mV, stand for 10min, 0.5C charge to 1.5V, stand for 10min, and cycle 50 times. 1C capacity retention rate = 1C discharge capacity / 0.1C discharge capacity, 2C capacity retention rate = 1C discharge capacity / 0.1C discharge capacity, and the test results are shown in Table 2.
[0179] 3) The silicon-based negative electrode active material of Example 1 and the premixed powder of Example 4 were tested by scanning electron microscope. The results are shown in Figure 3 and Figure 4 It can be seen that in the silicon-based negative electrode active material of Example 1 and the premixed powder of Example 4, the conductive material is attached to the silicon-based particles.
[0180] 4) Before the button half-cell was subjected to rate and cycle tests, the electrode prepared from the silicon-based negative electrode active material in Example 1 was subjected to scanning electron microscopy testing, and after 50 cycles, the electrode was subjected to scanning electron microscopy testing. The results are shown in Table 1. Figure 5 and Figure 6 .
[0181] Table 1
[0182]
[0183] Table 2
[0184]
[0185] From the above test results, it can be seen that in the silicon-based negative electrode active material or negative electrode composite active material of each embodiment, the conductive substance can be attached to the silicon-based particles with good adhesion, showing better conductivity, higher rate performance, and better cycle performance.
[0186] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0187] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A silicon-based electrode active material, characterized in that: The invention comprises silicon-based particles, an adhesive layer and a conductive material, wherein the conductivity of the conductive material is greater than that of the silicon-based particles, the conductive material is attached to the silicon-based particles through the adhesive layer, and can remain attached to the silicon-based particles during the expansion and contraction of the silicon-based particles.
2. The silicon-based electrode active material according to claim 1, characterized in that: The bonding layer covers the silicon-based particles, and the conductive material is independently dispersed in the bonding layer, or is located on the surface of the bonding layer, or is covered by the bonding layer.
3. The silicon-based electrode active material according to any one of claims 1 to 2, characterized in that The mass of the conductive substance accounts for 0.04% to 50% of the mass of the silicon-based electrode active material, and / or the mass of the bonding layer accounts for 0.04% to 50% of the mass of the silicon-based electrode active material.
4. The silicon-based electrode active material according to any one of claims 1 to 2, characterized in that The conductive material includes one or more of conductive carbon black, carbon nanotubes, graphene, carbon fibers, copper nanoparticles and silver nanoparticles; and / or the material of the bonding layer includes one or more of a polymer bonding material, a partial carbide of the polymer bonding material and a complete carbide of the polymer bonding material.
5. The silicon-based electrode active material according to claim 4, characterized in that: The structure of the polymer adhesive material includes one or more of acrylate group, carboxylic acid group, cyano group, amide group, hydroxyl group, benzene ring, carbon-carbon double bond, carbon-carbon triple bond, pyrrole, amine group and imine group.
6. The silicon-based electrode active material according to claims 1 to 2 and 5, characterized in that: Includes at least one of the following features: 1) The particle size D50 of the silicon-based particles satisfies: 0.1 μm ≤ D50 ≤ 30 μm; 2) The conductive material is irregularly shaped or spherical, and the particle size D50 satisfies: 0.01 μm ≤ D50 ≤ 10 μm; 3) The conductive material is in a fibrous or tubular shape, and the average length L satisfies: 0.05 μm ≤ D50 ≤ 100 μm, and the aspect ratio L / D satisfies: 1 ≤ L / D ≤ 200000; 4) The conductive material is in the form of a sheet, and the thickness h satisfies: 0.1nm≤h≤10μm, the maximum distance L1 between two points on the front side satisfies: 0.05μm≤L1≤100μm, and the maximum distance L2 between two points on the back side satisfies: 0.05μm≤L2≤100μm; 5) The conductive material is in the form of a strip, with a thickness h satisfying: 0.1 nm ≤ h ≤ 10 μm, an average length L satisfying: 0.05 μm ≤ L ≤ 100 μm, and an average width W satisfying: 1 nm ≤ W ≤ 50 μm; 6) The particle size D10 of the primary particles of the silicon-based electrode active material satisfies: 0.01 μm ≤ D10 ≤ 50 μm, the particle size D50 satisfies: 0.01 μm ≤ D50 ≤ 50 μm, and the particle size D90 satisfies: 0.01 μm ≤ D90 ≤ 50 μm; 7) The resistivity of the silicon-based electrode active material is 0.5Ω·mm~1500Ω·mm; 8) The silicon-based electrode active material is a silicon-based negative electrode active material.
7. The silicon-based electrode active material according to claims 1 to 2 and 4, characterized in that: The silicon-based particles include silicon and other elements and meet at least one of the following conditions: 1) The silicon content is 5wt%~95wt%; 2) The other elements include one or more of carbon, nitrogen, oxygen, fluorine, chlorine, phosphorus, sulfur, boron, copper, silver, titanium, zirconium, vanadium, molybdenum, tungsten, aluminum and iron.
8. An electrode composite active material, characterized in that: It comprises the silicon-based electrode active material and active particles according to any one of claims 1 to 7, wherein the active particles are independently and freely dispersed in the gaps of the silicon-based electrode active material, or are coated by the bonding layer, or are connected to the silicon-based particles through the bonding layer, or are connected to the conductive material through the bonding layer.
9. The electrode composite active material according to claim 8, characterized in that: The bonding layer covers the silicon-based particles and the active particles, and the conductive material is independently dispersed in the bonding layer, or is located on the surface of the bonding layer, or is covered by the bonding layer.
10. The electrode composite active material according to any one of claims 8 to 9, characterized in that: Each of the active particles meets the following conditions: 1) The theoretical specific capacity of the active particles is ≥ 100 mAh / g; 2) The electrical conductivity of the active particles is greater than that of the silicon-based particles; 3) The expansion rate of the active particles in a certain direction when fully intercalated with lithium is smaller than the expansion rate of the silicon-based particles in the same direction when fully intercalated with lithium.
11. The electrode composite active material according to claim 10, characterized in that: The active particles meet at least one of the following conditions: 1) The active particles account for 1% to 95% of the mass of the silicon-based electrode material; 2) The active particles include one or more of artificial graphite, natural graphite, hard carbon, soft carbon, carbon microspheres, lithium metal, lithium titanate, silicon-based materials and tin-based materials; 3) The particle size D50 of the active particles satisfies: 0.1 μm ≤ D50 ≤ 50 μm.
12. A method for preparing a silicon-based electrode active material, characterized in that: The following steps are involved: mixing silicon-based particles and a conductive substance to obtain a dry powder mixture, wherein the conductive substance has a greater conductivity than the silicon-based particles; Mixing the dry powder mixture, the binding material and the solvent to obtain a slurry having a solid content of 50 wt % to 90 wt %; After diluting the slurry, the solvent is removed, so that the bonding material forms a bonding layer, and the bonding layer attaches the conductive substance to the silicon-based particles and enables the conductive substance to remain attached to the silicon-based particles during the expansion and contraction of the silicon-based particles.
13. The method for preparing a silicon-based electrode active material according to claim 12, characterized in that: The method for removing the solvent is spray drying. Before spray drying, the slurry is diluted to a solid content of 1wt% to 50wt%.
14. The method for preparing a silicon-based electrode active material according to any one of claims 12 to 13, characterized in that: After removing the solvent, the method further comprises the following steps: heating to partially or completely carbonize the bonding material to form the bonding layer.
15. The method for preparing a silicon-based electrode active material according to claim 14, characterized in that: The heating temperature is 60℃~700℃.
16. A method for preparing an electrode composite active material, characterized in that: The method comprises the following steps: mixing a silicon-based electrode active material and active particles, wherein the silicon-based electrode active material is as described in any one of claims 1 to 7, or is prepared by the preparation method as described in any one of claims 12 to 15.
17. A method for preparing an electrode composite active material, characterized in that: The following steps are involved: mixing silicon-based particles, a portion of active particles and a conductive substance to obtain a dry powder mixture, wherein the conductive substance has a greater conductivity than the silicon-based particles; Mixing the dry powder mixture, the binding material and the solvent to obtain a slurry having a solid content of 50 wt % to 90 wt %; After diluting the slurry, the solvent is removed, so that the bonding material forms a bonding layer, the bonding layer attaches the conductive substance to the silicon-based particles, and enables the conductive substance to remain attached to the silicon-based particles during the expansion and contraction of the silicon-based particles, and the active particles are coated by the bonding layer, or connected to the silicon-based particles through the bonding layer, or connected to the conductive substance through the bonding layer, to obtain a premixed powder; Mix the premixed powder with the remaining portion of the active particles.
18. A method for preparing an electrode composite active material, characterized in that: The following steps are involved: mixing silicon-based particles, active particles and a conductive substance to obtain a dry powder mixture, wherein the conductive substance has a greater conductivity than the silicon-based particles; Mixing the dry powder mixture, the binding material and the solvent to obtain a slurry having a solid content of 50 wt % to 90 wt %; After diluting the slurry, the solvent is removed, so that the bonding material forms a bonding layer, and the bonding layer attaches the conductive substance to the silicon-based particles, and enables the conductive substance to remain attached to the silicon-based particles during the expansion and contraction of the silicon-based particles, and the active particles are coated by the bonding layer, or connected to the silicon-based particles through the bonding layer, or connected to the conductive substance through the bonding layer.
19. An electrode plate, characterized in that: It comprises a current collector and an electrode active layer located on the current collector, wherein the electrode active layer comprises the silicon-based electrode active material according to any one of claims 1 to 7, or comprises the electrode composite active material according to any one of claims 8 to 11, or comprises the silicon-based electrode active material prepared by the preparation method according to any one of claims 12 to 15, or comprises the electrode composite active material prepared by the preparation method according to any one of claims 16 to 18.
20. The electrode plate according to claim 19, characterized in that: The electrode active layer also includes a conductive agent and a binder.
21. A battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and the negative electrode sheet is as described in any one of claims 19 to 20, or comprises the silicon-based electrode active material according to any one of claims 1 to 7, or comprises the electrode composite active material according to any one of claims 8 to 11, or comprises the silicon-based electrode active material prepared by the preparation method according to any one of claims 12 to 15, or comprises the electrode composite active material prepared by the preparation method according to any one of claims 16 to 18.
Citation Information
Cited By
Silicon-based electrode active material, electrode composite active material, preparation method and use
WO2026144756A1